Evaluation eines digitalen Fachspezifischen Chinesischsprachkurses für Studierende des Ingenieurwesens - Hambach, Dennis (die hochschullehre. Interdisziplinäre Zeitschrift für Hochschule und Lehre)
Ziel dieser Studie ist es den digitalen moodlegestützten asynchronen Sprachkurs Fachspezifisches Chinesisch für das „Maschinenbau in China Programm“ (mb-cn) der Fakultät für Maschinenbau der Universität Paderborn zu evaluieren, um Handlungsempfehlungen für zukünftig ähnlich aufgebaute Projekte zu entwickeln. Dazu wurden im Sommersemester 2021 sechs leitfadengestützte Interviews geführt. Die Interviews wurden anschließend mithilfe von deduktiv ermittelten Kategorien, die sich aus dem Technology Acceptance Model 2 (TAM2) nach Venkatesh und Davis (2000) ergaben, nach Mayring (2015) analysiert, um abschließend die Forschungsfrage zu beantworten: „Wie bewerten mb-cn Ingenieurstudierende die wahrgenommene Nützlichkeit der digitalen Sprachlernangebote des Kurses Fachspezifisches Chinesisch?“.
Keywords: Technology Acceptance Model; Fachspezifische Chinesischsprachkurse; digitale Lehre; Moodle; Evaluation

Rezension zu: Michaela Eigmüller und Mathilde Wohlgemuth (Hrsg.): Schützen – Das Buch. 500 Jahre Kulturgeschichte in Süddeutschland, lllerbeuren 2021 - Leineweber, Jonas (Bayrisches Jahrbuch für Volkskunde)

Algorithms as complementary abstractions. Published online first 2022 - Matzner, Tobias (New Media & Society)

ROBOTER BAUEN, PROGRAMMIEREN LERNEN, DIGITALE KULTUREN VERSTEHEN — Christoph Engemann, Sylvia Kokot, Thomas Nyckel, Isabel Schmiedel, Mary Shnayien, Florian Sprenger über Arduino in medienwissenschaftlicher Lehre und Forschung - Engemann, Christoph; Kokot, Sylvia; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (Open Media Studies Blog)
Die Sonderreihe zu Forschen, Lehren und Lernen mit digitalen Tools setzt sich mit zwei Beiträgen aus dem Bochumer Virtual Humanities Lab (VHL) fort. Im ersten Teil geht es um das auf Obsidian beruhende Laborbuch, das die Forschungsprozesse und Forschungsdaten am VHL dokumentiert, vernetzt und veröffentlicht. Explizites Ziel ist es, damit auch die Sackgassen, Wiederholungen und Umwege dieser Forschung sichtbar zu machen. Der zweite Teil stellt Arduino-Bausätze vor, wie sie am VHL in Forschung und Lehre eingesetzt werden, um in der Hands-on-Auseinandersetzung mit informatischen und ingenieurwissenschaftlichen Artefakten und Methoden einen erweiterten Zugang zu digitalen Kulturen zu eröffnen.

FORSCHUNG (BE-)SCHREIBEN — Christoph Engemann, Sylvia Kokot, Thomas Nyckel, Isabel Schmiedel, Mary Shnayien, Florian Sprenger über medienwissenschaftliche Laborbücher - Engemann, Christoph; Kokot, Sylvia; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (Open Media Studies Blog)
Die Sonderreihe zu Forschen, Lehren und Lernen mit digitalen Tools setzt sich mit zwei Beiträgen aus dem Bochumer Virtual Humanities Lab (VHL) fort. Im ersten Teil geht es um das auf Obsidian beruhende Laborbuch, das die Forschungsprozesse und Forschungsdaten am VHL dokumentiert, vernetzt und veröffentlicht. Explizites Ziel ist es, damit auch die Sackgassen, Wiederholungen und Umwege dieser Forschung sichtbar zu machen. Der zweite Teil stellt Arduino-Bausätze vor, wie sie am VHL in Forschung und Lehre eingesetzt werden, um in der Hands-on-Auseinandersetzung mit informatischen und ingenieurwissenschaftlichen Artefakten und Methoden einen erweiterten Zugang zu digitalen Kulturen zu eröffnen.

Arduino - Engemann, Christoph; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (The Lab Book. Situated Practices in Media Studies)

"Die sehen mich als irgendwas zwischen Schulsozialarbeiter und Sonderpädagoge" - Ergebnisse einer Interviewstudie zur Rolle pädagogischer Fachkräfte in multiprofessionellen Teams an inklusive Schulen - Grüter, Sandra; Hölz, Svenja; Neumann, Phillip; Lütje-Klose, Birgit (Zeitschrift für Inklusion)
Keywords: Multiprofessionelle Teams; Kooperation; Professionalisierung; Schulentwicklung; Inklusion

Boosting artificial intelligence in design processes by the use of additive manufacturing - Ott, Manuel; Meihöfener, Niclas; Koch, Rainer (Proceedings of the 33rd Annual International Solid Freeform Fabrication Symposium 2022)
Additive manufacturing offers the option of converting digital prototypes into real structures as quickly as possible by the special property of tool-free manufacturing. However, this process can only be used at optimum speed if bottlenecks can be effectively avoided. One of these constraints is the design process. Although modern CAD systems allow a significant increase in many areas, this always requires a person with specific skills (e.g. engineer). In the field of AM in particular, more and more powerful software solutions have recently been published which accelerate the Design for Additive Manufacturing, including most CAD-tasks. In many areas, therefore, attempts are already made to automate relevant design steps as much as possible, more and more using neural networks and artificial intelligence. This paper presents how and why such techniques can be used to generate three-dimensional structures quickly and efficiently in cases of deep generative design tasks.

Small-scale online simulations in guided-wave photonics - Hammer, Manfred (Integrated Optics: Devices, Materials, and Technologies XXVI)
Online solvers for a series of standard 1-D or 2-D problems in integrated optics will be discussed. Implemented on the basis of HTML/JavaScript/SVG with core routines compiled from well tested C++-sources, the quasi-analytical algorithms require a computational load that can be handled easily even by current mobile devices. So far the series covers the 1-D guided modes of dielectric multilayer slab waveguides and the oblique plane wave reflection from these, the modes of rectangular channel waveguides (in an approximation of effective indices), bend modes of curved multilayer slabs, whispering-gallery resonances (“Quasi-Normal-Modes”) supported by circular dielectric cavities, the hybrid modes of circular multi-step-index optical fibers, bound and leaky modes of 1-D complex multilayers, including plasmonic surface modes, and, with restrictions, quite general rectangular scattering problems in 2-D.
Keywords: tet_topic_waveguide

Quasiparticle energies and optical response of RbTiOPO4 and KTiOAsO4 - Neufeld, Sergej; Schindlmayr, Arno; Schmidt, Wolf Gero (Journal of Physics: Materials)
Many-body perturbation theory based on density-functional theory calculations is used to determine the quasiparticle band structures and the dielectric functions of the isomorphic ferroelectrics rubidium titanyl phosphate (RbTiOPO4) and potassium titanyl arsenide (KTiOAsO4). Self-energy corrections of more than 2 eV are found to widen the transport band gaps of both materials considerably to 5.3 and 5.2 eV, respectively. At the same time, both materials are characterized by strong exciton binding energies of 1.4 and 1.5 eV, respectively. The solution of the Bethe-Salpeter equation based on the quasiparticle energies results in onsets of the optical absorption within the range of the measured data.

Electrochemical performance of KTiOAsO_4 (KTA) in potassium-ion batteries from density-functional theory - Bocchini, Adriana; Gerstmann, Uwe; Bartley, Tim; Steinrück, Hans-Georg; Henkel, Gerald; Schmidt, Wolf Gero (Phys. Rev. Materials)

Transareales Gedenken an genozidale Geschichte in Analogie zum islamistischen Terror der Gegenwart in "Das Dorf" des algerischen Autors Boualem Sansal" - Müller, Inez

Analysis of the Segregation Phenomena of Wood Fiber Reinforced Plastics - Moritzer, Elmar; Flachmann, Felix; Richters, Maximilian; Neugebauer, Marcel (Journal of Composites Science)
Wood–plastic composites (WPC) are enjoying a steady increase in popularity. In addition to the extrusion of decking boards, the material is also used increasingly in injection molding. Depending on the formulation, geometry and process parameters, WPC tends to exhibit irregular filling behavior, similar to the processing of thermosets. In this work, the influence of matrix material and wood fiber content on the flow, mold filling and segregation behavior of WPC is analyzed. For this purpose, investigations were carried out on a flow spiral and a sheet cavity. WPC based on thermoplastic polyurethane (TPU) achieves significantly higher flow path lengths at a wood mass content of 30% than polypropylene (PP)-based WPC. The opposite behavior occurs at higher wood contents due to the different shear thinning behavior. Slightly decreased wood contents could be observed at the beginning of the flow path and greatly increased wood contents at the end of the flow path, compared to the starting material. When using the plate cavity, flow anomalies in the form of free jets occur as a function of the wood content, with TPU exhibiting the more critical behavior. The flow front is frayed, but in contrast to the flow spiral, no significant wood accumulation could be detected due to the shorter flow path lengths.
Keywords: Engineering (miscellaneous); Ceramics and Composites

Dynamic modeling of absorption/desorption closed-loop including periphery - Bothe, Mike; Hami Dindar, Iman; Lutters, Nicole; Kenig, Eugeny Y. (Computers and Chemical Engineering)

Konzept für ein hierarchisches autonomes Verkehrsmanagement - Mertin, Sven

Data-Driven Models for Control Engineering Applications Using the Koopman Operator - Junker, Annika; Timmermann, Julia; Trächtler, Ansgar (2022 3rd International Conference on Artificial Intelligence, Robotics and Control (AIRC 2022))
Within this work, we investigate how data-driven numerical approximation methods of the Koopman operator can be used in practical control engineering applications. We refer to the method Extended Dynamic Mode Decomposition (EDMD), which approximates a nonlinear dynamical system as a linear model. This makes the method ideal for control engineering applications, because a linear system description is often assumed for this purpose. Using academic examples, we simulatively analyze the prediction performance of the learned EDMD models and show how relevant system properties like stability, controllability, and observability are reflected by the EDMD model, which is a critical requirement for a successful control design process. Subsequently, we present our experimental results on a mechatronic test bench and evaluate the applicability to the control engineering design process. As a result, the investigated methods are suitable as a low-effort alternative for the design steps of model building and adaptation in the classical model-based controller design method.
Keywords: Koopman Operator; Nonlinear Control; Extended Dynamic Mode Decomposition; Hybrid Modelling

Composed Physics- and Data-driven System Identification for Non-autonomous Systems in Control Engineering - Götte, Ricarda-Samantha; Timmermann, Julia (2022 3rd International Conference on Artificial Intelligence, Robotics and Control (AIRC))
In control design most control strategies are model-based and require accurate models to be applied successfully. Due to simplifications and the model-reality-gap physics-derived models frequently exhibit deviations from real-world-systems. Likewise, purely data-driven methods often do not generalise well enough and may violate physical laws. Recently Physics-Guided Neural Networks (PGNN) and physics-inspired loss functions separately have shown promising results to conquer these drawbacks. In this contribution we extend existing methods towards the identification of non-autonomous systems and propose a combined approach PGNN-L, which uses a PGNN and a physics-inspired loss term (-L) to successfully identify the system's dynamics, while maintaining the consistency with physical laws. The proposed method is demonstrated on two real-world nonlinear systems and outperforms existing techniques regarding complexity and reliability.
Keywords: data-driven; physics-based; physics-informed; neural networks; system identification; hybrid modelling

Phase identification in twin-roll cast Al-Li alloys - BAJTOŠOVÁ, Lucia; Grydin, Olexandr; STOLBCHENKO, Mykhailo; Schaper, Mirko; KŘIVSKÁ, Barbora; KRÁLÍK, Rostislav; ŠLAPÁKOVÁ, Michaela; CIESLAR, Miroslav (METAL 2022 Conference Proeedings)
Al-Li-based alloys are an attractive material for aircraft and aerospace applications. Preparation of these alloys by twin-roll casting (TRC), which combines rapid metal solidification and subsequent plastic reduction in a single processing step, could improve the properties of the alloys compared to materials prepared by conventional direct-chill casting. A commonly used approach for identifying primary phases is a chemical analysis by energy dispersive spectroscopy (EDS). More accurate results can be achieved by combining the method with diffraction analysis. This process can be considerably simplified in microscopes equipped with automated crystal orientation and phase mapping (ACOM-TEM). Al-Cu-Li-Mg-Zr alloy was prepared by twin-roll casting. A combination of TEM and STEM images with chemical analysis by EDS and ACOM-TEM was used to obtain complex information about phases of boundary primary particles. The efficiency of the individual methods for the phase identification in TRC Al-Li-based alloys is discussed.
Keywords: Al-Cu-Li-M-Zr-Fe alloy; twin-roll casting; phase identification; ACOM-TEM

Optical Detection of Phase Transformations in Steels: An Innovative Method for Time-Efficient Material Characterization During Tailored Thermo-mechanical Processing of a Press Hardening Steel - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Metallurgical and Materials Transactions A)
Abstract With an innovative optical characterization method, using high-temperature digital image correlation in combination with thermal imaging, the local change in strain and change in temperature could be determined during thermo-mechanical treatment of flat steel specimens. With data obtained by this optical method, the transformation kinetics for every area of interest along the whole measuring length of a flat specimen could be analyzed by the generation of dilatation curves. The benefit of this innovative optical characterization method compared to a dilatometer test is that the experimental effort for the design of a tailored component could be strongly reduced to the investigation of only a few tailored thermo-mechanical processed specimens. Due to the implementation of a strain and/or temperature gradient within the flat specimen, less metallographic samples are prepared for hardness analysis and analysis of the microstructural composition by scanning electron microscopy to investigate the influence of different process parameters. Compared to performed dilatometer tests in this study, the optical method obtained comparable results for the transformation start and end temperatures. For the final design of a part with tailored properties, the optical method is suitable for a time-efficient material characterization. Graphical Abstract
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics

Microstructure transformations in a press hardening steel during tailored thermo‐mechanical processing - Westermann, Hendrik; Reitz, Alexander; Mahnken, Rolf; Schaper, Mirko; Grydin, Olexandr (steel research international)

Low Cycle Fatigue Performance of Additively Processed and Heat-Treated Ti-6Al-7Nb Alloy for Biomedical Applications - Hein, Maxwell; Kokalj, David; Lopes Dias, Nelson Filipe; Stangier, Dominic; Oltmanns, Hilke; Pramanik, Sudipta; Kietzmann, Manfred; Hoyer, Kay-Peter; Meißner, Jessica; Tillmann, Wolfgang; Schaper, Mirko (Metals)
In biomedical engineering, laser powder bed fusion is an advanced manufacturing technology, which enables, for example, the production of patient-customized implants with complex geometries. Ti-6Al-7Nb shows promising improvements, especially regarding biocompatibility, compared with other titanium alloys. The biocompatible features are investigated employing cytocompatibility and antibacterial examinations on Al2O3-blasted and untreated surfaces. The mechanical properties of additively manufactured Ti-6Al-7Nb are evaluated in as-built and heat-treated conditions. Recrystallization annealing (925 °C for 4 h), β annealing (1050 °C for 2 h), as well as stress relieving (600 °C for 4 h) are applied. For microstructural investigation, scanning and transmission electron microscopy are performed. The different microstructures and the mechanical properties are compared. Mechanical behavior is determined based on quasi-static tensile tests and strain-controlled low cycle fatigue tests with total strain amplitudes εA of 0.35%, 0.5%, and 0.8%. The as-built and stress-relieved conditions meet the mechanical demands for the tensile properties of the international standard ISO 5832-11. Based on the Coffin–Manson–Basquin relation, fatigue strength and ductility coefficients, as well as exponents, are determined to examine fatigue life for the different conditions. The stress-relieved condition exhibits, overall, the best properties regarding monotonic tensile and cyclic fatigue behavior.
Keywords: General Materials Science; Metals and Alloys; laser powder bed fusion; Ti-6Al-7Nb; titanium alloy; biomedical engineering; low cycle fatigue; microstructure; nanostructure

Numerical investigation of the clinched joint loadings considering the initial pre-strain in the joining area - Martin, Sven; Bielak, Christian Roman; Bobbert, Mathias; Tröster, Thomas; Meschut, Gerson (Production Engineering)
The components of a body in white consist of many individual thin-walled sheet metal parts, which usually are manufactured in deep-drawing processes. In general, the conditions in a deep-drawing process change due to changing tribology conditions, varying degrees of spring back, or scattering material properties in the sheet blanks, which affects the resulting pre-strain. Mechanical joining processes, especially clinching, are influenced by these process-related pre-strains. The final geometric shape of a clinched joint is affected to a significant level by the prior material deformation when joining with constant process parameters. That leads to a change in the stiffness and force transmission in the clinched joint due to the different geometric dimensions, such as interlock, neck thickness and bottom thickness, which directly affect the load bearing capacity. Here, the influence of the pre-straining in the deep drawing process on the force distribution in clinch points in an automotive assembly is investigated by finite-element models numerically. In further studies, the results are implemented in an optimization tool for designing clinched components. The methodology starts with a pre-straining of metal sheets. This step is followed by 2D rotationally symmetric forming simulations of the joining process. The resulting mesh of each forming simulation is rotated and 3D models are obtained. The clinched joint solid model with pre-strains is used further to determine the joint stiffnesses. With the simulation of the same test set-up with an equivalent point-connector model, the equivalent stiffness for each pre-strain combination is determined. Simulations are performed on a clinched component to assess the influence of pre-strain and sheet thinning on the clinched joint loadings by using the equivalent stiffnesses. The investigations clearly show that for the selected component, the loadings at the clinch points are dependent on the sheet thinning and the stiffnesses due to pre-strain. The magnitude of the influence varies depending on the quantity considered. For example, the shear force is more sensitive to the joint stiffness than to the sheet thinning.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Influence of the Surrounding Sheet Geometry on a Clinched Joint - Martin, Sven; Kurtusic, Kristijan; Tröster, Thomas (Key Engineering Materials)

Influence of Physical Vapor Deposition on High-Cycle Fatigue Performance of Additively Manufactured Ti-6Al-7Nb Alloy - Hein, Maxwell (Crystals)

Powder Spread Flaws in Polymer Laser Sintering and its Influences on Mechanical Performance - Klippstein, Sven Helge; Schmid, Hans-Joachim (Proceedings of the 33nd Annual International Solid Freeform Fabrication Symposium)
By monitoring the recoating process within polymer laser sintering production, it was shown that multiple powder-spread-flaws can be detected. Those groove-like flaws are expected to be the result of agglomerates jamming between the recoater and the last powder layer. This work is analyzing the interaction between powder-spread-flaws and part properties, showing the influence of the recoating process on the performance of laser sintering parts. Therefore, artificial powder-spread-flaws are applied to the build jobs of tensile test specimens which are measured and analyzed regarding the elongation at break, strength and fracture position. For the characteristics of the flaws, the artificial grooves are varied in depth and width. Furthermore, the position of the flaw is changed form mid part to close to surface areas. It was shown, that several flaws are visible at the part surface, resulting in stress concentration and reduced performance. But there are as well parts with flaw-layers, which are not visible after the build process on the part. Those parts can have significantly reduced mechanical properties as well.
Keywords: Selective Sasersintering; Process Monitoring; Powder Spread

Fortschrittskontrolle der Modellierung mechatronischer Produkte - Gräßler, Iris; Wiechel, Dominik; Thiele, Henrik (Tagungsband der Fachtagung VDI-Mechatronik)
Die Anforderungen an die Entwicklung mechatronischer Systeme sind seit der Erstfassung der VDI Richtlinie 2206 im Jahr 2004 stetig gestiegen. Nach einer umfassenden Überarbeitung ist 2021 die Richtline im Weißdruck neu veröffentlicht worden. Neben dem Systemdenken als gestärktes Kernelement des V-Modells und sechs Kontrollpunkten nur Gliederung der sachlogischen Aufgaben ist die durchgängig explizite „Modellierung und Analyse“ eine wesentliche Neuerung der Richtlinie. Da sich die Kontrollfragen nur auf den Entwicklungsprozess im Ganzen beziehen, wird durch die Betrachtung der Modellierung eines Batteriesystems aus einem Entwicklungsprojekt eines deutschen Automobilherstellers die folgende Forschungsfrage betrachtet: Welche spezifischen Kontrollfragen zu Fortschritt und Reifegrad der Modellierung eines Batteriesystems können aus den Kontrollpunkten des V-Modells (VDI 2206:2020) gefolgert werden? Als Ergebnis der Forschung liegen hinsichtlich der Modellierung eines spezifischen Systems detaillierte Kontrollfragen vor, die eine methodische Unterstützung für die modellbasierte Systementwicklung komplexer mechatronischer Systeme bieten. Zusätzlich ermöglichen sie der Projektleitung die Überprüfung des aktuellen Status der Entwicklung und sichern die Vollständigkeit des Systemmodells ab.

Model-driven Design and Management of Professional Education Programmes - Wolters, Dennis; Engels, Gregor (ICSOB'22 Companion Proceedings)

Heat Treatments of Metastable β Titanium Alloy Ti-24Nb-4Zr-8Sn Processed by Laser Powder Bed Fusion - Hein, Maxwell; Lopes Dias, Nelson Filipe; Pramanik, Sudipta; Stangier, Dominic; Hoyer, Kay-Peter; Tillmann, Wolfgang; Schaper, Mirko (Materials)

Tab2Onto: Unsupervised Semantification with Knowledge Graph Embeddings - Zahera, Hamada Mohamed Abdelsamee; Heindorf, Stefan; Balke, Stefan; Haupt, Jonas; Voigt, Martin; Walter, Carolin; Witter, Fabian; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: ESWC 2022 Satellite Events)

CausalQA: A Benchmark for Causal Question Answering - Bondarenko, Alexander; Wolska, Magdalena; Heindorf, Stefan; Blübaum, Lukas; Ngonga Ngomo, Axel-Cyrille; Stein, Benno; Braslavski, Pavel; Hagen, Matthias; Potthast, Martin (Proceedings of the 29th International Conference on Computational Linguistics)
At least 5% of questions submitted to search engines ask about cause-effect relationships in some way. To support the development of tailored approaches that can answer such questions, we construct Webis-CausalQA-22, a benchmark corpus of 1.1 million causal questions with answers. We distinguish different types of causal questions using a novel typology derived from a data-driven, manual analysis of questions from ten large question answering (QA) datasets. Using high-precision lexical rules, we extract causal questions of each type from these datasets to create our corpus. As an initial baseline, the state-of-the-art QA model UnifiedQA achieves a ROUGE-L F1 score of 0.48 on our new benchmark.

Lernerkorpora als Ressource in der quantitativen DaF-Forschung - Weber, Tassja (Vermitteln – Verbinden – Verstehen)

A High-Fidelity Flow Solver for Unstructured Meshes on Field-Programmable Gate Arrays: Design, Evaluation, and Future Challenges - Karp, Martin; Podobas, Artur; Kenter, Tobias; Jansson, Niclas; Plessl, Christian; Schlatter, Philipp; Markidis, Stefano (International Conference on High Performance Computing in Asia-Pacific Region)

Parallel quantum chemistry on noisy intermediate-scale quantum computers - Schade, Robert; Bauer, Carsten; Tamoev, Konstantin; Mazur, Lukas; Plessl, Christian; Kühne, Thomas (Phys. Rev. Research)
A parallel hybrid quantum-classical algorithm for the solution of the quantum-chemical ground-state energy problem on gate-based quantum computers is presented. This approach is based on the reduced density-matrix functional theory (RDMFT) formulation of the electronic structure problem. For that purpose, the density-matrix functional of the full system is decomposed into an indirectly coupled sum of density-matrix functionals for all its subsystems using the adaptive cluster approximation to RDMFT. The approximations involved in the decomposition and the adaptive cluster approximation itself can be systematically converged to the exact result. The solutions for the density-matrix functionals of the effective subsystems involves a constrained minimization over many-particle states that are approximated by parametrized trial states on the quantum computer similarly to the variational quantum eigensolver. The independence of the density-matrix functionals of the effective subsystems introduces a new level of parallelization and allows for the computational treatment of much larger molecules on a quantum computer with a given qubit count. In addition, for the proposed algorithm techniques are presented to reduce the qubit count, the number of quantum programs, as well as its depth. The evaluation of a density-matrix functional as the essential part of our approach is demonstrated for Hubbard-like systems on IBM quantum computers based on superconducting transmon qubits.

Towards electronic structure-based ab-initio molecular dynamics simulations with hundreds of millions of atoms - Schade, Robert; Kenter, Tobias; Elgabarty, Hossam; Lass, Michael; Schütt, Ole; Lazzaro, Alfio; Pabst, Hans; Mohr, Stephan; Hutter, Jürg; Kühne, Thomas; Plessl, Christian (Parallel Computing)
Keywords: Artificial Intelligence; Computer Graphics and Computer-Aided Design; Computer Networks and Communications; Hardware and Architecture; Theoretical Computer Science; Software

Effects of verbal negation on TVA’s capacity and weight parameters - Banh, Ngoc Chi; Scharlau, Ingrid (TeaP 2022 - Abstracts of the 64th Conference of Experimental Psychologists)

Folgen wiederholter Negation auf die Aufmerksamkeit - Banh, Ngoc Chi; Scharlau, Ingrid; Rohlfing, Katharina J. (52. Kongress der Deutschen Gesellschaft für Psychologie)

Backward error analysis for variational discretisations of partial differential equations - McLachlan, Robert I; Offen, Christian (Journal of Geometric Mechanics)
In backward error analysis, an approximate solution to an equation is compared to the exact solution to a nearby ‘modified’ equation. In numerical ordinary differential equations, the two agree up to any power of the step size. If the differential equation has a geometric property then the modified equation may share it. In this way, known properties of differential equations can be applied to the approximation. But for partial differential equations, the known modified equations are of higher order, limiting applicability of the theory. Therefore, we study symmetric solutions of discretized partial differential equations that arise from a discrete variational principle. These symmetric solutions obey infinite-dimensional functional equations. We show that these equations admit second-order modified equations which are Hamiltonian and also possess first-order Lagrangians in modified coordinates. The modified equation and its associated structures are computed explicitly for the case of rotating travelling waves in the nonlinear wave equation.

Symplectic integration of learned Hamiltonian systems - Offen, Christian; Ober-Blöbaum, Sina (Chaos: An Interdisciplinary Journal of Nonlinear Science)
Hamiltonian systems are differential equations which describe systems in classical mechanics, plasma physics, and sampling problems. They exhibit many structural properties, such as a lack of attractors and the presence of conservation laws. To predict Hamiltonian dynamics based on discrete trajectory observations, incorporation of prior knowledge about Hamiltonian structure greatly improves predictions. This is typically done by learning the system's Hamiltonian and then integrating the Hamiltonian vector field with a symplectic integrator. For this, however, Hamiltonian data needs to be approximated based on the trajectory observations. Moreover, the numerical integrator introduces an additional discretisation error. In this paper, we show that an inverse modified Hamiltonian structure adapted to the geometric integrator can be learned directly from observations. A separate approximation step for the Hamiltonian data avoided. The inverse modified data compensates for the discretisation error such that the discretisation error is eliminated. The technique is developed for Gaussian Processes.

Die Förderung von Reflexionskompetenz und Reflexion durch die angeleitete Bearbeitung eines weiterentwicklungsorientierten Online-Self-Assessments - Buhl, Heike M.; Sagolla, Nils; Bohndick, Carla (Lehrerbildung auf dem Prüfstand)

CovidPubGraph: A FAIR Knowledge Graph of COVID-19 Publications - Pestryakova, Svetlana; Vollmers, Daniel; Sherif, Mohamed; Heindorf, Stefan; Saleem, Muhammad; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (Scientific Data)

„LauRa - In der Lehramtsausbildung Reflexionskompetenz analysieren“ : Untersuchungen zum Verhältnis von Theorie, Praxis und Reflexion im Rahmen der Professionalisierung angehender Lehrpersonen - Meier, Jana

Die Kraft der Bilder. Funktionen neuer Illustrationen bei Übersetzungen. Kathleen Vereecken – Alles komt goed, altijd (2018) | Alles wird gut, immer (2021) - Lammer, Christina
Keywords: Kathleen Vereecken; Kinder- und Jugendliteratur; Krieg; Belgien

Dequantizing the Quantum Singular Value Transformation: Hardness and Applications to Quantum Chemistry and the Quantum PCP Conjecture - Gharibian, Sevag; Gall, François Le (Proceedings of the 54th ACM Symposium on Theory of Computing (STOC))
The Quantum Singular Value Transformation (QSVT) is a recent technique that gives a unified framework to describe most quantum algorithms discovered so far, and may lead to the development of novel quantum algorithms. In this paper we investigate the hardness of classically simulating the QSVT. A recent result by Chia, Gily\'en, Li, Lin, Tang and Wang (STOC 2020) showed that the QSVT can be efficiently "dequantized" for low-rank matrices, and discussed its implication to quantum machine learning. In this work, motivated by establishing the superiority of quantum algorithms for quantum chemistry and making progress on the quantum PCP conjecture, we focus on the other main class of matrices considered in applications of the QSVT, sparse matrices. We first show how to efficiently "dequantize", with arbitrarily small constant precision, the QSVT associated with a low-degree polynomial. We apply this technique to design classical algorithms that estimate, with constant precision, the singular values of a sparse matrix. We show in particular that a central computational problem considered by quantum algorithms for quantum chemistry (estimating the ground state energy of a local Hamiltonian when given, as an additional input, a state sufficiently close to the ground state) can be solved efficiently with constant precision on a classical computer. As a complementary result, we prove that with inverse-polynomial precision, the same problem becomes BQP-complete. This gives theoretical evidence for the superiority of quantum algorithms for chemistry, and strongly suggests that said superiority stems from the improved precision achievable in the quantum setting. We also discuss how this dequantization technique may help make progress on the central quantum PCP conjecture.

Turn all the lights off: Bright- and dark-field second-harmonic microscopy to select contrast mechanisms for ferroelectric domain walls - Hegarty, Peter A.; Beccard, Henrik; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Recent analyses by polarization resolved second-harmonic (SH) microscopy have demonstrated that ferroelectric (FE) domain walls (DWs) can possess non-Ising wall characteristics and topological nature. These analyses rely on locally analyzing the properties, directionality, and magnitude of the second-order nonlinear tensor. However, when inspecting FE DWs with SH microscopy, a manifold of different effects may contribute to the observed signal difference between domains and DWs, i.e., far-field interference, Čerenkov-type phase-matching (CSHG), and changes in the aforementioned local nonlinear optical properties. They all might be present at the same time and, therefore, require careful interpretation and separation. In this work, we demonstrate how the particularly strong Čerenkov-type contrast can selectively be blocked using dark- and bright-field SH microscopy. Based on this approach, we show that other contrast mechanisms emerge that were previously overlayed by CSHG but can now be readily selected through the appropriate experimental geometry. Using the methods presented, we show that the strength of the CSHG contrast compared to the other mechanisms is approximately 22 times higher. This work lays the foundation for the in-depth analysis of FE DW topologies by SH microscopy.
Keywords: General Physics and Astronomy

Nonlinear optical interactions in focused beams and nanosized structures - Amber, Zeeshan H.; Spychala, Kai J.; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Thin-film materials from μm thickness down to single-atomic-layered 2D materials play a central role in many novel electronic and optical applications. Coherent, nonlinear optical (NLO) μ-spectroscopy offers insight into the local thickness, stacking order, symmetry, or electronic and vibrational properties. Thin films and 2D materials are usually supported on multi-layered substrates leading to (multi-)reflections, interference, or phase jumps at interfaces during μ-spectroscopy, which all can make the interpretation of experiments particularly challenging. The disentanglement of the influence parameters can be achieved via rigorous theoretical analysis. In this work, we compare two self-developed modeling approaches, a semi-analytical and a fully vectorial model, to experiments carried out in thin-film geometry for two archetypal NLO processes, second-harmonic and third-harmonic generation. In particular, we demonstrate that thin-film interference and phase matching do heavily influence the signal strength. Furthermore, we work out key differences between three and four photon processes, such as the role of the Gouy-phase shift and the focal position. Last, we can show that a relatively simple semi-analytical model, despite its limitations, is able to accurately describe experiments at a significantly lower computational cost as compared to a full vectorial modeling. This study lays the groundwork for performing quantitative NLO μ-spectroscopy on thin films and 2D materials, as it identifies and quantifies the impact of the corresponding sample and setup parameters on the NLO signal, in order to distinguish them from genuine material properties.<
Keywords: General Physics and Astronomy

Ba(BO2OH) – A Monoprotonated Monoborate from Hydroflux Showing Intense Second Harmonic Generation - Li, Yuxi; Hegarty, Peter A.; Rüsing, Michael; Eng, Lukas M.; Ruck, Michael (Zeitschrift für anorganische und allgemeine Chemie)
Abstract Pure samples of colorless, air‐stable Ba(BO 2 OH) crystals were obtained from Ba(NO 3 ) 2 and H 3 BO 3 under the ultra‐alkaline conditions of a KOH hydroflux at about 250 °C. The product formation depends on the water‐base molar ratio and the molar ratio of the starting materials. B(OH) 3 acts as a proton donor (Brønsted acid) rather than a hydroxide acceptor (Lewis acid). Ba(BO 2 OH) crystallizes in the non‐centrosymmetric orthorhombic space group P 2 1 2 1 2 1 . Hydrogen bonds connect the almost planar (BO 2 OH) 2− anions, which are isostructural to HCO 3 − , into a syndiotactic chain. IR and Raman spectroscopy confirm the presence of hydroxide groups, which are involved in weak hydrogen bonds. Upon heating in air to about 450 °C, Ba(BO 2 OH) dehydrates to Ba 2 B 2 O 5 . Moreover, the non‐centrosymmetric structure of Ba(BO 2 OH) crystals was verified with power‐dependent confocal Second Harmonic Generation (SHG) microscopy indicating large conversion efficiencies in ambient atmosphere.
Keywords: Inorganic Chemistry

Tuning the Čerenkov second harmonic contrast from ferroelectric domain walls via anomalous dispersion - Hegarty, Peter A.; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Second harmonic (SH) microscopy represents a powerful tool for the investigation of crystalline systems, such as ferroelectrics and their domain walls (DWs). Under the condition of normal dispersion, i.e., the refractive index at the SH wavelength is larger as compared to the refractive index at the fundamental wavelength, n(2ω)>n(ω), bulk crystals will generate no SH signal. Should the bulk, however, contain DWs, an appreciable SH signal will still be detectable at the location of DWs stemming from the Čerenkov mechanism. In this work, we demonstrate both how SH signals are generated in bulk media and how the Čerenkov mechanism can be inhibited by using anomalous dispersion, i.e., n(ω)<n(2ω). This allows us to quantitatively estimate the relative strength of the Čerenkov compared to other SH contrast mechanisms in DWs, such as the interference contrast. The results are in agreement with previous experiments based on the geometric separation of the signals. Due to the observed, strong Čerenkov contrast, such signal contributions may not be neglected in polarimetry studies of ferroelectric DWs in the future.
Keywords: General Physics and Astronomy

Ein Blick auf: Verstetigung und Transfer im Bundesprogramm „Kita-Einstieg: Brücken bauen in frühe Bildung“ - Albers, Timm; Hoeft, Maike; Abendroth, Sonja; Meusel, Sarah

Erkenntnisse zu Verstetigung und Transfer im Bundesprogramm "Kita-Einstieg: Brücken bauen in frühe Bildung" - Abendroth, Sonja; Hoeft, Maike; Meusel, Sarah

SA-SDR: A Novel Loss Function for Separation of Meeting Style Data - von Neumann, Thilo; Kinoshita, Keisuke; Boeddeker, Christoph; Delcroix, Marc; Haeb-Umbach, Reinhold (ICASSP 2022 - 2022 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

MMS-MSG: A Multi-purpose Multi-Speaker Mixture Signal Generator - Cord-Landwehr, Tobias; von Neumann, Thilo; Boeddeker, Christoph; Haeb-Umbach, Reinhold (2022 International Workshop on Acoustic Signal Enhancement (IWAENC))
The scope of speech enhancement has changed from a monolithic view of single, independent tasks, to a joint processing of complex conversational speech recordings. Training and evaluation of these single tasks requires synthetic data with access to intermediate signals that is as close as possible to the evaluation scenario. As such data often is not available, many works instead use specialized databases for the training of each system component, e.g WSJ0-mix for source separation. We present a Multi-purpose Multi-Speaker Mixture Signal Generator (MMS-MSG) for generating a variety of speech mixture signals based on any speech corpus, ranging from classical anechoic mixtures (e.g., WSJ0-mix) over reverberant mixtures (e.g., SMS-WSJ) to meeting-style data. Its highly modular and flexible structure allows for the simulation of diverse environments and dynamic mixing, while simultaneously enabling an easy extension and modification to generate new scenarios and mixture types. These meetings can be used for prototyping, evaluation, or training purposes. We provide example evaluation data and baseline results for meetings based on the WSJ corpus. Further, we demonstrate the usefulness for realistic scenarios by using MMS-MSG to provide training data for the LibriCSS database.

Monaural source separation: From anechoic to reverberant environments - Cord-Landwehr, Tobias; Boeddeker, Christoph; von Neumann, Thilo; Zorila, Catalin; Doddipatla, Rama; Haeb-Umbach, Reinhold (2022 International Workshop on Acoustic Signal Enhancement (IWAENC))
Impressive progress in neural network-based single-channel speech source separation has been made in recent years. But those improvements have been mostly reported on anechoic data, a situation that is hardly met in practice. Taking the SepFormer as a starting point, which achieves state-of-the-art performance on anechoic mixtures, we gradually modify it to optimize its performance on reverberant mixtures. Although this leads to a word error rate improvement by 7 percentage points compared to the standard SepFormer implementation, the system ends up with only marginally better performance than a PIT-BLSTM separation system, that is optimized with rather straightforward means. This is surprising and at the same time sobering, challenging the practical usefulness of many improvements reported in recent years for monaural source separation on nonreverberant data.

Rezension von: Viola Schrader: Historisches Denken und sprachliches Handeln. Eine qualitativ-empirische Untersuchung von Schülertexten. Münster et al.: LIT 2021 - Hartung, Olaf (sehepunkte)

On Synchronization of Wireless Acoustic Sensor Networks in the Presence of Time-Varying Sampling Rate Offsets and Speaker Changes - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (ICASSP 2022 - 2022 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Warping of Radar Data Into Camera Image for Cross-Modal Supervision in Automotive Applications - Grimm, Christopher; Fei, Tai; Warsitz, Ernst; Farhoud, Ridha; Breddermann, Tobias; Haeb-Umbach, Reinhold (IEEE Transactions on Vehicular Technology)
We present an approach to automatically generate semantic labels for real recordings of automotive range-Doppler (RD) radar spectra. Such labels are required when training a neural network for object recognition from radar data. The automatic labeling approach rests on the simultaneous recording of camera and lidar data in addition to the radar spectrum. By warping radar spectra into the camera image, state-of-the-art object recognition algorithms can be applied to label relevant objects, such as cars, in the camera image. The warping operation is designed to be fully differentiable, which allows backpropagating the gradient computed on the camera image through the warping operation to the neural network operating on the radar data. As the warping operation relies on accurate scene flow estimation, we further propose a novel scene flow estimation algorithm which exploits information from camera, lidar and radar sensors. The proposed scene flow estimation approach is compared against a state-of-the-art scene flow algorithm, and it outperforms it by approximately 30% w.r.t. mean average error. The feasibility of the overall framework for automatic label generation for RD spectra is verified by evaluating the performance of neural networks trained with the proposed framework for Direction-of-Arrival estimation.

Technically enabled explaining of voice characteristics - Wiechmann, Jana; Glarner, Thomas; Rautenberg, Frederik; Wagner, Petra; Haeb-Umbach, Reinhold (18. Phonetik und Phonologie im deutschsprachigen Raum (P&P))

Long‐term effects of institutional conditions on perceived corruption – A study on organizational imprinting in post‐communist countries - Auer, Thorsten Fabian; Knorr, Karin; Thommes, Kirsten (Business Ethics, the Environment & Responsibility)
In this paper, we apply imprinting theory to examine how institutional transformation substantially influences perceptions of corruption that we argue to be incorporated to a varying extent in organizations founded in that period. For this purpose, we compare the effect of a sudden shock (dissolution of the Soviet Union) on the managers' present perceptions to that of a steady transition (EU accession). We consult the 5th round of the Business Environment and Enterprise Performance Survey from 2012 to 2014 analyzing 4715 interviews with managers of organizations from twelve Central and Eastern European countries. Our results reveal striking differences in the present perception of corruption for organizations founded immediately before and immediately after these institutional transitions. The study's results contribute to the research on imprinting theory regarding the relationship between organizations and institutional conditions that constitutes a lasting effect on organizational structures. Thus, applying an institutional perspective that considers less stable periods for organizations yields a promising avenue in research on organizational behavior.
Keywords: Central and Eastern Europe; corruption; imprinting theory; institutional transformation; shock-imprinting

Die Wirksamkeit von Lernzielen für Studienleistungen – eine experimentelle Studie - Auer, Thorsten Fabian (die hochschullehre)
According to the German Rectors’ Conference (HRK), German higher education teaching fails to meet the demand to integrate competence-oriented learning objectives. Despite a wide-ranging debate on the use of learning objectives, empirical research on their effectiveness is scarce. The present study uses the features of digital teaching platforms to investigate the perception and effectiveness of learning objectives applying a randomised controlled experiment followed by a survey in a course for undergraduate economics students (N = 30). Controlling group preconditions and the treatment effect allows to draw conclusions about the different learning outcomes of the student groups. The specification of behaviour-oriented learning objectives in the online course system leads to significantly better performance in the treatment group. A stronger perception of the learning objectives in the treatment group supports this effect that remains significant in a regression analysis. Thus, the study provides an empirical justification to integrate learning objectives in university teaching.
Keywords: learning objectives; academic performance; perception; teaching methods; experiment

An approach to teaching data science in middle school - Podworny, Susanne; Fleischer, Yannik (Proceedings of the 15th international conference on technology in mathematics teaching (ICTMT 15))

Teaching machine learning with decision trees in middle school using CODAP - Fleischer, Yannik; Podworny, Susanne (Proceedings of the 15th international conference on technology in mathematics teaching (ICTMT 15))

An example of rich, real and multivariate survey data for use in school - Podworny, Susanne; Fleischer, Yannik; Stroop, Dietlinde; Biehler, Rolf

Lydia Böttger (Universität Paderborn) rezensiert: Michalak, Magdalena; Döll, Marion (Hrsg.) (2021): Lehrwerke und Lehrmaterialien im Kontext des Deutschen als Zweitsprache und der sprachlichen Bildung. [Deutsch als Zweitsprache Positionen, Perspektiven, Potenziale, Bd. 2]. Münster, New York: Waxmann, 164 Seiten. ISBN 978-3-8309-4105-7. - Böttger, Lydia (www.daz-portal.de)

Investigation into Target Speaking Rate Adaptation for Voice Conversion - Kuhlmann, Michael; Seebauer, Fritz; Ebbers, Janek; Wagner, Petra; Haeb-Umbach, Reinhold (Interspeech 2022)

Schorsch Kamerun: „Extra Vages machen wir aus tiefer Überzeugung“. - Jacke, Christoph (Kaput. Magazin für Insolvenz & Pop.)

Effective vocabulary learning apps: what should they look like? An evaluation with a particular view to German language acquisition - Lentfort, Theresa; Künzl-Snodgrass, Annemarie; de Vincent-Humphreys, Maren (Ab Initio Language Teaching in British Higher Education. The Case of German)

Informed vs. Blind Beamforming in Ad-Hoc Acoustic Sensor Networks for Meeting Transcription - Gburrek, Tobias; Schmalenstroeer, Joerg; Heitkaemper, Jens; Haeb-Umbach, Reinhold (2022 International Workshop on Acoustic Signal Enhancement (IWAENC))

A Meeting Transcription System for an Ad-Hoc Acoustic Sensor Network - Gburrek, Tobias; Boeddeker, Christoph; von Neumann, Thilo; Cord-Landwehr, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold

Threshold Independent Evaluation of Sound Event Detection Scores - Ebbers, Janek; Haeb-Umbach, Reinhold; Serizel, Romain (Proceedings of the IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
Performing an adequate evaluation of sound event detection (SED) systems is far from trivial and is still subject to ongoing research. The recently proposed polyphonic sound detection (PSD)-receiver operating characteristic (ROC) and PSD score (PSDS) make an important step into the direction of an evaluation of SED systems which is independent from a certain decision threshold. This allows to obtain a more complete picture of the overall system behavior which is less biased by threshold tuning. Yet, the PSD-ROC is currently only approximated using a finite set of thresholds. The choice of the thresholds used in approximation, however, can have a severe impact on the resulting PSDS. In this paper we propose a method which allows for computing system performance on an evaluation set for all possible thresholds jointly, enabling accurate computation not only of the PSD-ROC and PSDS but also of other collar-based and intersection-based performance curves. It further allows to select the threshold which best fulfills the requirements of a given application. Source code is publicly available in our SED evaluation package sed_scores_eval.

KI im Einsatz. Interdisziplinäre Herausforderungen im Projekt UAV-Rescue - Philippi, Martina; Heusinger-Heß, Victoria; Ari, Meral; Krüger, Emily (Mensch und Computer 2022 - Workshopband)
Im Projekt „UAV-Rescue: UAV-getragene Sensorik zur KI-basierten Unterstützung von Rettungsmissionen“ wird an einem unbemannt fliegenden System geforscht, das in schwer zugänglichen Räumen bei der Rettungspriorisierung hilft, indem es den Einsatzkräften eine Visualisierung des Raumes mit darin lokalisierten Lebenszeichen zur Verfügung stellt. Diese neue Technologie wirft verschiedene ethische Fragestellungen auf, die unter anderem die Nutzung von Künstlicher Intelligenz zur Lebenszeichendetektion und die Einbettung der neuen Technologie in die Einsatzpraxis betreffen. Die ethische Begleitforschung des Projekts adressiert diese Fragestellungen in einem interdisziplinären und iterativen Diskurs mit Technikpartnern und Endanwendern. Einige dieser Fragestellungen werden hier vor dem Hintergrund der eingesetzten KI-Methoden und der bestehenden Einsatzpraxis beim THW vorgestellt.
Keywords: rescue robotics; interdisciplinarity; artifical intelligence; ethics

Same Different but not Same Same: Ethnic Discrimination in Application Procedures in the German Public Sector - Auer, Thorsten Fabian; Ekemen, Helin; Hagedorn, Carolin; Heise, Chantal; Rese, Christine (Empirical Economics Letters)
Regulations to prevent ethnic discrimination in accessing the labor market are implemented most thoroughly in the public sector. However, it remains to be assessed if these regulations are internalized. We conducted a field experiment to examine ethnic discrimination when applying for internships in German municipalities by unsolicited inquiries. We compared responses in German cities to Turkish, Italian, and German applicants in two periods, and find consistent disadvantages for the Turkish and Italian applicants as well as differences related to gender. Thus, the likelihood for ethnic discrimination rises when applying for positions in public institutions that are not subject to regulations.
Keywords: Ethnic Discrimination; Public Sector; Field Experiment; Application Procedure

Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

Smart cities and smart governance models for future cities - Nastjuk, I.; Trang, S.; Papageorgiou, E. (Electronic Markets)

Konzeptpapier zur Konferenz "Geschichte im digitalen Wandel? Geschichtskultur – Erinnerungspraktiken – Historisches Lernen"

Produktkennzeichnung durch lokal definierte Einstellung von ferromagnetischen Eigenschaften beim Drückwalzen von metastabilen Stahlwerkstoffen - Arian, Bahman; Homberg, Werner; Kersting, Lukas; Trächtler, Ansgar; Rozo Vasquez, Julian (36. Aachener Stahlkolloquium – Umformtechnik “Ideen Form geben“)

A flow forming process model to predict workpiece properties in AISI 304L - Arian, Bahman; Oesterwinter, Annika; Homberg, Werner; Rozo Vasquez, Julian; Walther, Frank; Kersting, Lukas; Trächtler, Ansgar (19th Int. Conference on Metal Forming 2022)

"Die Bombardierung von Brüssel - teil 2" (Podcast) - Huybrechts, Yves

"Das Museum der BSD in Soest. Ein Interview mit Burkhard Schnettler" - Huybrechts, Yves

Autonomes Putten mittels datengetriebener und physikbasierter Methoden - Junker, Annika; Fittkau, Niklas; Timmermann, Julia; Trächtler, Ansgar (Proceedings - 32. Workshop Computational Intelligence: Berlin, 1. - 2. Dezember 2022)

Zum Potential von Lernmaterial für den Einsatz im konfessionell-kooperativen Religionsunterricht: eine qualitative Inhaltsanalyse von Unterrichtsentwürfen zum Thema Märtyrerinnen und Märtyrer - Hüster, Jonas Maximilian

Kooperation von Elternhaus und Schule zum Thema "digitale Medien". Unterschiede zwischen Elternhäusern und Zusammenhänge mit elterlichen Fähigkeiten zur Nutzung und Gestaltung des Internets sowie Medienerziehung - Bonanati, Sabrina; Kurock, Ricarda; Gruchel, Nicole; Buhl, Heike M. (MedienPädagogik)
Die Kooperation zwischen Elternhaus und Schule kann Eltern in ihren Fähigkeiten zur Internetnutzung und -gestaltung sowie in der Wahl passender Medienerziehungsstrategien ihrer Kinder unterstützen. Voraussetzung dafür ist Wissen darüber, welche Kooperationsangebote Eltern von Schulen zum Thema digitale Medien erhalten. Die vorliegende Studie untersuchte anhand einer Befragung von N = 736 Schülerinnen und Schülern der fünften Klassenstufe und N = 426 ihrer Eltern, welche Informations- und Teilhabeangebote letztere erhielten und wie diese Angebote mit elterlichen Fähigkeiten zur Nutzung und Gestaltung des Internets sowie Medienerziehung zusammenhängen. Eltern erhielten nur zum Teil Informations- und Teilhabeangebote zum Thema ‹digitale Medien›. Eltern mit Migrationshintergrund und Eltern mit niedrigeren bis mittleren Bildungsabschlüssen berichteten aber, häufiger Angebote zu erhalten. Je häufiger Eltern Angebote erhielten, bei denen sie digitale Medien mit ihren Kindern zusammen ausprobieren und erproben konnten, umso geringer waren Fähigkeiten zur Internetnutzung. Dies kann mit der Passung der Angebote von Schulen zu den Bedürfnissen von Eltern zusammenhängen, aber auch ein Anzeichen dafür sein, dass gerade Eltern mit geringeren Fähigkeiten auf Kooperationsangebote von Schulen eingehen. Es wurden keine signifikanten Zusammenhänge zwischen Kooperationsangeboten und Medienerziehung gefunden. Ergebnisse können helfen, vermehrte Angebote für Eltern zu schaffen sowie adressatengerecht zu gestalten.

Family Climate and Social Adaptation of Adolescents in Community Samples: A Systematic Review - Kurock, Ricarda; Gruchel, Nicole; Bonanati, Sabrina; Buhl, Heike M. (Adolescent Research Review)
The family plays an important role in adolescents’ social development. Yet there is little information about the impact of family climate on adolescents’ social adaptation, and the term “family climate” is seldom clearly defined and is usually related to other concepts, such as family systems or family environments. To understand the core of family climate, this study conducted a systematic review to analyze research about family climate associated with adolescents’ social adaptation in community samples. A search of empirical research published over the last 20 years identified 12 relevant studies. The studies revealed that family climate can mainly be described in terms of cohesion, conflict, organization, adaptability, and expressiveness. Family climate was shown to be a good predictor of both problem-solving skills and violence in relationships and exhibited further associations with other aspects of social adaptation. This review revealed a need for more systematic and longitudinal research on family climate in community samples.
Keywords: Family environment; Family system; Adolescents; Social adaptation; Systematic review

Einleitung - Haacke-Werron, Stefanie; Karsten, Andrea; Scharlau, Ingrid (Reflexive Schreibwissenschaft. Disziplinäre und praktische Perspektiven)

Sprechen, Schreiben, Denken - Karsten, Andrea (Reflexive Schreibwissenschaft. Disziplinäre und praktische Perspektiven)

Learning Data-Driven PCHD Models for Control Engineering Applications* - Junker, Annika; Timmermann, Julia; Trächtler, Ansgar (IFAC-PapersOnLine)
Keywords: Control and Systems Engineering

Museen sind wie Denkmäler - Hartung, Olaf (BBBank-Magazin Wertsache)
Keywords: Museum Geschichte Exponate

VALIDATION AND COMPARISON OF FEM-SIMULATION RESULTS OF THE FUSED DEPOSITION MODELING PROCESS UNDER CONSIDERATION OF DIFFERENT MESH RESOLUTIONS - Moritzer, Elmar; Hecker, Felix (Proceedings of the 33rd Annual Freeform Fabrication Symposium)

The broken chain: Evidence against emotionally driven upstream indirect reciprocity - Schnedler, Wendelin (Games and Economic Behavior)
Psychologists claim that being treated kindly puts individuals in a positive emotional state: they then treat an unrelated third party more kindly. Numerous experiments document that subjects indeed ‘pay forward’ specific behavior. For example, they are less generous after having experienced stinginess. This, however, is not necessarily driven by emotions. Subjects may also imitate what they regard as socially adequate behavior. Here, I present an experiment in which imitation is not possible at the next opportunity to act with a stranger: after being given either a fun or an annoying job, subjects have to decide whether to be generous or not. I find that although subjects who are given the annoying job report more negative emotions than those with the fun job, they do not treat an unrelated third person more unkindly in terms of passing on less money.
Keywords: Economics and Econometrics; Finance

Transfer Pricing Rules for Intangibles: Implementation and Practical Challenges - Safaei, Reyhaneh

Changes in Transfer Pricing Regulations and Corporate Investment Decisions - Shabestari, Mehrzad Azmi; Safaei, Reyhaneh

Effects of spherical fillers on the processability and mechanical properties of PA613 and PP-based LS dry blends - Kletetzka, Ivo; Gawlikowicz, Roland; Schmid, Hans-Joachim (Proceedings of the 33th Annual International Solid Freeform Fabrication Symposium)
In this work, the influences of spherical fillers on the processing properties and the resulting mechanical properties of laser sintered components are investigated. For this purpose, micro glass spheres, hollow glass bubbles and mineral spheres are dry blended to the matrix polymers polyamide 613 and polypropylene with a filling ratio of 20 and 40 vol%. First, relevant properties of the blends, such as powder flowability, thermal behavior and melt viscosity, are investigated. Based on the results, processing parameters are then developed for the LS process and the mechanical properties of the components are investigated. The aim is to be able to tailor the mechanical properties of LS components by adding fillers and thus to create new application areas for additively manufactured components.

Shelf Life of Polyamide 12 (PA2200) Laser Sintering Powder - Kletetzka, Ivo; Klippstein, Sven Helge; Schmid, Hans-Joachim (Proceedings of the 33th Annual International Solid Freeform Fabrication Symposium)

Evaluation of the Ecological Footprint for Parts from AlSi10Mg manufactured by Laser Powder Bed Fusion - Bödger, Christian; Weiss, Christian; Schiefer, Ekkehard; Heussen, Daniel; Haefner, Constantin (Proceedings of the 33rd Annual International Solid Freeform Fabrication Symposium – An Additive Manufacturing Conference)
The manufacturing industry contributes immensely to the global emissions and therefore is a key factor that has to be addressed when a more sustainable production is desired. Laser Powder Bed Fusion (LPBF) is an AM technique that offers the possibility to manufacture metal parts in a more material efficient way due to the layer-by-layer build-up. Nevertheless, the processing chain for parts from LPBF contains additional steps like powder atomization, which also influence the ecological footprint of the production chain. Within this work, a life-cycle model for the production step of parts from AlSi10Mg powder material is developed. The model is supplied with data from the powder atomization up to the production step, either by literature, database or experimental measurements during production. The footprint in terms of CO2 emissions is then analyzed and emission-intense steps are identified. Two manufacturing scenarios are considered to evaluate the sensitivity on the emissions.

“Christoph Besold on Confederation Rights and Duties of Esteem in Diplomatic Relations.” - Blank, Andreas (Intellectual History Review)

“Pufendorf and Leibniz on Duties of Esteem in Diplomatic Relations.” - Blank, Andreas (Journal of International Political Theory)

“Esteem and Self-Esteem in Early Modern Ethics and Politics. An Overview.” - Blank, Andreas (Intellectual History Review)

“On Reconstructing Leibniz’s Metaphysics.” - Blank, Andreas (Hungarian Philosophical Review)

Beste Bedingungen für junge Ökonominnen und Ökonomen? Neue Daten und Empfehlungen der AG Nachwuchs im Verein für Socialpolitik - Bayer, Christian; Engelmaier, Florian; Riphahn, Regina T.; Schmidt-Dengler, Philipp; Sondergeld, Virgina; Sureth-Sloane, Caren; von Wangenheim, Jonas; Weizsäcker, Georg

Lehrer*innenbilder in Autosozioanalysen. Die Emergenzfunktion von Lehrer*innen als abwesende Dritte - Haker, Christoph; Otterspeer, Lukas (Bilder von Lehrer*innenberuf und Schule (Mediale) Entwürfe zwischen Produktion, Rezeption und Aneignung)

Grenzbearbeitungen – methodologische Überlegungen zu einer sozialwissenschaftlichen Forschungsperspektive - Haker, Christoph; Otterspeer, Lukas (Grenzen auflösen – Grenzen ziehen: Grenzbearbeitungen zwischen Erziehungswissenschaft, Politik und Gesellschaft)

Antiakademismus heute - Haker, Christoph; Otterspeer, Lukas; Schildknecht, Lukas (Demokratie unter Druck)